Immaginario: spazio e tempo della cura. Dal Rêve-Eveillé all’ Esperienza Immaginativa (Altre Modernità, 2012)
Object of interest and philosophical speculation, sometimes examined as in contrast to the perception and knowledge, Imaginary has generated, in the history of thought, conflicting theories that have defined it, alternately, positive enhancer of knowledge or element disturbing element of pure and  rational knowledge, a real obstacle to the learning process. Years of psychotherapy that, since the Rêve-Eveillè of Desoille (1930) led us to the current definition of Imaginative Experience, have confirmed, as stated Desoille, that the psychotherapy with the imaginative experience is a privileged way to approach the unconscious. Privileged way, in which the contributions of neuroscience, through the studies of neural substrate (Passerini, 2009) and a new explanation of neuro- psycho - biological imaginative phenomenon, have allowed us to identify a new way of working. Psychotherapy with Imaginative Experience, psychodynamic model based on the privileged use of the imaginative production, exploits Imaginary as the main place of the treatment. It is situated within a theoretical framework referable to the depth psychology, since it interacts and mobilizes psychic energies that when are conflictual, traumatic or deficient, can lead to suffering. Beyond the resolution of the symptoms, the methodology with Imaginative Experience, through a specifically structured psychodynamic setting, allows to recover the subjectivity of the individual who, at the beginning of the treatment, is suffering from the disease and is calling for help. It also allows to bring to mind, through movement in the imaginative place, "all the scattered elements of the psyche in order to make a synthesis" (Desoille). The stimulating imagination, born of the therapeutic relationship between two individual who interact since they need love, to be loved and recognized for their values ​​and meanings, leads to conflictual and unconscious areas. That can trigger real transformative movement that is the result of the creative function of Imaginary, and that has already been recognized in the mid-twentieth century by Gaston Bachelard who declared: "Imagine is a fundamental mental activity" (1975).
Keywords: Psychotherapy; Cure; Unconscious; Awakened-dream; Images; Desoille; Girep; Sispi